Stakeholder engagement, knowledge problems and ethical challenges - Mitchell, J. Robert (Journal of business ethics, 2022)
In the management and business ethics literatures, stakeholder engagement has been demonstrated to lead to more ethical management practices. However, there may be limits on the extent to which stakeholder engagement can, as currently conceptualized, resolve some of the more difficult ethical challenges faced by managers. In this paper we argue that stakeholder engagement, when seen as a way of reducing five types of knowledge problems - risk, ambiguity, complexity, equivocality, and a priori irreducible uncertainty - can aid managers in resolving such ethical challenges. Using a practical illustration of the ethical challenges surrounding the development and application of genetic modification technologies, we demonstrate how stakeholder engagement enables managers to better address these knowledge problems, thereby to manage more ethically. In this way, we suggest that stakeholder engagement has an even more crucial role to play in business ethics research and practice.